Distributions, compositions, and ecological risk assessment of polycyclic aromatic hydrocarbons and phthalic acid esters in surface sediment of Songhua river, China. (March 2020) - Yang, Yanyan; Wang, Haiyan; Chang, Yang; Yan, Guokai; Chu, Zhaosheng; Zhao, Zhuanjun; Li, Li; Li, Zewen; Wu, Tong
Abstract: The distribution, composition, and ecological risk of 16 types of polycyclic aromatic hydrocarbons (PAHs) and 6 types of phthalic acid esters (PAEs) in the surface sediment of Songhua river, northeast China, were investigated. The total weight of the PAHs (∑16 PAHs) varied from 226.70 to 7086.62 ng/g dry weight (dw), whereas that of the PAEs (∑6 PAEs) ranged from 819.44 to 24, 035.39 ng/g dw. The dominant PAHs were four-membered ring PAHs, which varied from 18.65% to 78.10% of the total PAHs. The most abundant PAEs was di-2-ethylhexyl phthalate ester (DEHP), which accounted for 65.02–99.07% of the total PAEs, followed by di-n-butyl phthalate ranging from 1.50 to 55.43%. Pyrolytic origin was the dominant PAH source. Approximately 12.70% target PAHs in the Songhua river sediment exhibited moderate ecological risk with 23.49–1404.09 ng/g carcinogenic toxicity equivalent. DEHP in 80.95% of the sediment samples exceeded the effects range low, indicating its potential harmfulness to the aquatic environment. Highlights: PAHs and PAEs in the Songhua river sediment were investigated. The dominant PAHs were 4 rings PAHs and most abundant PAEs was DEHP. 12.70% target PAHs in the Songhua river exhibited moderate ecological risk. The DEHP of 80.95% sediment samples exceeded the ERL. Pyrolytic origin was the dominant PAHs source.